Establishing soundscape preference criteria for urban shopping street design in Kuala Lumpur, Malaysia - Abdul Hamid, Nor Hamizah (2022)
Many of the attempts in Malaysia to address environmental noise pollution issues focus on lowering the sound level using the environmental noise management approach and environmental impact assessment. Nevertheless, the country’s noise pollution problems persist. The soundscape approach, a more constructive way to deal with the problem of noise pollution, applies in the early stage of the design process. However, in the absence of proper soundscape preference criteria in Malaysia, thus, the main aim of this study is to establish soundscape preference criteria for urban shopping street design in Kuala Lumpur. The methodological design used was quantitative research involving descriptive analysis, most and least preferred soundscape analysis, preference dimension analysis, analysis of differences and analysis of relationships. Based on field survey and observation data, which includes 411 respondents throughout three urban shopping streets in Kuala Lumpur, the statistical analyses suggest that various factors influence the subjective evaluations of soundscape perception, noise sensitivity, sound sources and context. This study is divided into three objectives: to identify the user’s preference for soundscape in urban shopping streets, to identify the key factors that influence the user’s preference of soundscape in urban shopping streets and to determine the relationships that exist among the soundscape, noise sensitivity, context, and sound source. The first objective highlighted three soundscape preference criteria: eventfulness, appropriateness, and calmness. The most preferred soundscape is varied, changing and lively. The second objective confirms that the subjective evaluations of site environmental patterns are also relevant to the soundscape evaluations with significant results on the day, weather, and sound level. In contrast, background, and behavioural factors, except for the visiting frequency, are insignificant. The third objective has discovered that visual perception and the visual quality of the environment are strong predictors of the user’s soundscape perception. The soundscape preference criteria devised at the end of this thesis come with 40 validated factors: the 22 soundscape perceptions, six visual perceptions, three visual quality, four perceived sound sources, and five urban sound environments. The present study results are essential for urban designers and planners by providing soundscape criteria to improve design solutions for noise pollution in urban shopping streets soundscapes.